Optimalisasi Manajemen Sistem Informasi pada UMKM: Pendekatan Framework COBIT 5 untuk Peningkatan Kualitas - Bahri, Ramadhan Syaeful; Putra, Yeffry Handoko (Labkat Press KA FTIK UNIKOM, 2023)
This study aims to establish a framework for governing information systems in Micro, Small, and Medium Enterprises (MSMEs), focusing on decision-making processes in advanced and emerging MSME clusters. COBIT 5 is employed to identify variables and guide the research stages. The research will specifically examine MSMEs located in Bandung District. The evaluation of governance quality for each target, which includes Nurtured MSMEs and Advanced MSMEs, involves utilizing the Process Assessment Model (PAM) derived from COBIT 5. In addition to gathering preliminary data through interviews and surveys conducted in Bandung District, this initial investigation also involved a comparative analysis of various methods employed in prior research about the study's subject matter. The findings from this study reveal that the data processing procedures for MSMEs in the Bandung Regency involve the use of computer/laptop devices. However, certain MSMEs face challenges in adequately managing the acquired data, emphasizing the necessity for more effective data management to ensure the produced data attains the quality required for constructing a model for advanced MSMEs. On the contrary, some other MSMEs in the Bandung Regency exhibit proficient data management practices, conducting regular evaluations of data and information, and basing their decisions on the analyzed data. These two scenarios serve as benchmarks for understanding the decision-making processes of both emerging and advanced MSMEs about data. The aspiration is that the outcomes of this study can serve as a benchmark, offering best practices for MSMEs to enhance the quality of their Decision-Making and achieve excellence in their business operations.